Four year follow up of aortic valve replacement for isolated aortic stenosis: a link between reduction in pressure overload, regression of left ventricular hypertrophy, and diastolic function. Issue 3 (1st September 2001) - Ikonomidis, I; Tsoukas, A; Parthenakis, F; Gournizakis, A; Kassimatis, A; Rallidis, L; Nihoyannopoulos, P
Abstract : OBJECTIVE: To evaluate changes in left ventricular function and the impact of ventricular hypertrophy and pressure gradient early and late after aortic valve replacement in patients with isolated aortic stenosis. DESIGN: 41 patients with isolated aortic stenosis and normal systolic function underwent cross sectional and Doppler echocardiography two months before and two weeks and four years after aortic valve replacement. RESULTS: Early after the operation, left ventricular mass index (mean (SD)) decreased from 187 (44) g/m 2 to 179 (46) g/m 2, because of a reduction in end diastolic diameter (p < 0.05). Aortic pressure gradients were reduced, as expected. Isovolumic relaxation time was reduced from 93 (20) ms to 78 (12) ms, and deceleration time from 241 (102) ms to 205 (77) ms (p < 0.05). At four years, left ventricular mass index was further reduced to 135 (30) g/m 2 (p < 0.01) as a result of wall thickness reduction in the interventricular septum (from 14 (1.6) mm to 12 (1.4) mm, p < 0.01) and the posterior wall (from 14 (1.6) mm to 12 (1.3) mm, p < 0.01). Diastolic function, expressed by a reduction in isovolumic relaxation time from 93 (20) ms to 81 (15) ms (p < 0.01) and deceleration time from 241 (102) ms to 226 (96) ms (p < 0.05), remained improved. Prolonged isovolumic relaxation time was associated with significant septal and posterior wall hypertrophy (wall thickness > 13 mm) (p < 0.05), whereas prolonged deceleration time was related to high residual gradient (peak gradient > 30 mm Hg ) (p < 0.01). CONCLUSIONS: Left ventricular diastolic function improves early after surgery for aortic stenosis in parallel with the reduction in the aortic gradient. However, prolongation of Doppler indices of myocardial relaxation and ventricular filling is observed in patients with significant left ventricular hypertrophy and a residual pressure gradient early after surgery. At four years postoperatively, diastolic function remains improved.